Differences between water permeability of astomatous and stomatous cuticular membranes: effects of air humidity in two species of contrasting drought-resistance strategy - Karbulková, Jana; Schreiber, Lukas; Macek, Petr; Santrucek, Jirí (Journal of experimental botany, 2008)
Cuticular water permeabilities of adaxial and abaxial leaf surfaces and their dependence on relative air humidity (RH) applied in long-term and short-term regimes have been analysed for Hedera helix, native in a temperate climate, and Zamioculcas zamiifolia, native in subtropical regions. The water permeability of cuticular membranes (CM) isolated from the adaxial (astomatous) and abaxial (stomatous) leaf sides was measured using a method which allowed the separation of water diffusion through the remnants of the original stomatal pores from water diffusion through the solid cuticle. The long-term effects of low (20-40%) or high (60-80%) RH applied during plant growth and leaf ontogeny ('growth RH') and the short-term effects of applying 2% or 100% RH while measuring permeability ('measurement RH') were investigated. With both species, water permeability of the solid stomatous CM was significantly higher than the permeability of the astomatous CM. Adaxial cuticles of plants grown in humid air were more permeable to water than those from dry air. The adaxial CM of the drought-tolerant H. helix was more permeable and more sensitive to growth RH than the adaxial CM of Z. zamiifolia, a species avoiding water stress. However, permeability of the solid abaxial CM was similar in both species and independent of growth RH. The lack of a humidity response in the abaxial CM is attributed to a higher degree of cuticular hydration resulting from stomatal transpiration. The ecophysiological significance of higher permeability of the solid stomatous CM compared to the astomatous CM is discussed.
Keywords: permeabilita buněčné membrány; Droughts; období sucha; vlhkost; voda; Cell Membrane Permeability; Water; Humidity; břečťan; Araceae; Hedera; Plant Leaves; listy rostlin